2022
DOI: 10.1103/physrevapplied.17.054048
|View full text |Cite
|
Sign up to set email alerts
|

Improved Vertical Carrier Transport for Green III-Nitride LEDs Using (In,Ga)N Alloy Quantum Barriers

Abstract: We report on experimental and simulation-based results using (In, Ga)N alloy quantum barriers in c-plane green light-emitting diode (LED) structures as a means to improve vertical carrier transport and reduce forward voltage (V F ). Three-dimensional device simulations that include random alloy fluctuations are used to understand carrier behavior in a disordered potential. The simulated current density-voltage (J -V) characteristics and modified electron-hole overlap |F mod | 2 indicate that increasing the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Furthermore, B 0 , C p and C n will also be carrier density dependent [18,52,53]. We follow here the widely made assumption that these coefficients are constant across the InGaN MQW region [23,25]. In the following we take a weighted average of parameters calculated in Ref.…”
Section: Appendix B: Recombinationmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, B 0 , C p and C n will also be carrier density dependent [18,52,53]. We follow here the widely made assumption that these coefficients are constant across the InGaN MQW region [23,25]. In the following we take a weighted average of parameters calculated in Ref.…”
Section: Appendix B: Recombinationmentioning
confidence: 99%
“…Experimental and theoretical studies on the electronic [15][16][17] and optical [18,19] properties of (In,Ga)N systems have already revealed that these properties are significantly impacted by alloy fluctuation induced carrier localization effects. However, the impact of alloy disorder on the carrier transport has only been targeted recently [20][21][22][23][24][25]. Here, studies are ranging from fully atomistic quantum mechanical approaches [20] up to modified continuum-based models [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the polarization barriers and band offsets increase for longer wavelength LEDs such that large driving voltages are required for vertical transport. These large driving voltages could result in large junction biases, where a significant proportion of the injected electrons could overflow the QWs directly to the p-side of the diode [13,39].…”
Section: Challenges Of Long-wavelength Gan-based Ledsmentioning
confidence: 99%